2014
DOI: 10.1158/1078-0432.14aacriaslc-b16
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B16: The effect of e-cigarette exposure on airway epithelial cell gene expression and transformation.

Abstract: Lung cancer is the leading cause of cancer-related mortality in the United States. Despite a strong correlation between cigarette smoking and the onset of lung cancer, the prevalence of smoking still remains high. Strategies to eliminate cigarette smoking have led to the emergence of new tobacco-related products as alternatives for cigarette smoking or tools for smoking cessation. The electronic cigarette (ECIG) is a battery-powered electronic nicotine delivery system (ENDS) designed to deliver nicotine withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…Although the nature and degree of harm associated with e-cigarette use is not fully known, emerging evidence suggests potential acute 7 and chronic 8 effects. One significant concern is the potential for e-cigarettes to serve as a precursor to combustible cigarette use, 910 which is an enormous public health burden.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Although the nature and degree of harm associated with e-cigarette use is not fully known, emerging evidence suggests potential acute 7 and chronic 8 effects. One significant concern is the potential for e-cigarettes to serve as a precursor to combustible cigarette use, 910 which is an enormous public health burden.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…However, it is unknown what happens to the lung when these constituents are heated and inhaled. E-cig heated PG can be converted to propylene oxide (1, 153), which is an irritant and an International Agency for Research on Cancer group 2b carcinogen (possibly carcinogenic to humans) (154). Heated VG and PG can be converted to acrolein, acetaldehyde, and formaldehyde, which also are known strong irritants that affect inflammation (155157).…”
Section: Introductionmentioning
confidence: 99%
“…The potential interactions of ENDS with cytotoxic cancer therapeutics are also unknown, and there is in vitro evidence that nicotine stimulates proliferation, migration, invasion, and angiogenesis and decreases cancer cell death from irradiation and chemotherapy, raising concern as to whether prolonged ENDS use might have similar effects in patients with cancer (78). Moreover, researchers have found that human bronchial cells grown in medium exposed to e-cigarette aerosol showed a similar pattern of gene expression to those grown in medium exposed to tobacco smoke (79). Whereas ENDS may have unknown adverse effects in cancer patients, the adverse effects of smoking are not in question.…”
mentioning
confidence: 99%